Новая псилоконопа (Diptera, Limoniidae) из Западной Сибири - Савченко, Е.Н. (Вестник зоологии, 1982)
Symplecta (Psiloconopa) trilaciniata S a v . , s p . n. from Western Siberia (Tyumen Region) is described. The species belongs to the S. (P.) meigeni (Ztt.) group and differs from all other known Falcarcuc species or the group mates Dw seminitid abdomen and. especially, by verv stout, strongly darkened, distally three-lobed outer dististyles male. _vDe s D e c i m e n s are preserved in the Institute of Zoology, Academy of Sciences, Ukrainian SSR (Kiev).